Pengaruh Media Baamboozle terhadap Hasil Belajar SKI Materi Hijrah Nabi di MI Madinatul Ulum Tembelang Jombang - Fikroh, Faza Mufidatul; Ashoumi, Hilyah (MASALIQ, 2025)
This study aims to determine the effect of the media Baamboozle on the learning outcomes of Islamic History (SKI) students in Phase B regarding the material "The Migration of the Prophet Muhammad (SAW) to Yatsrib." The background of this research is the decline in SKI learning outcomes caused by learning that tends to be boring. This study uses a quantitative approach with a pre-experimental research design of the one group pretest posttest design type, which consists of one experimental group that is given a pretest and posttest, without a control class. The sample taken includes all students from class four B. The research instrument consists of a test comprising ten multiple-choice questions and five essay questions. Data collection techniques were conducted through observation and tests of student learning outcomes. Data analysis uses Homogeneity Test, Normality Test, and t-Test. The conclusion of this study indicates that there is an effect of using the Baamboozle media on the learning outcomes of SKI students in class four B on the material "The Migration of the Prophet Muhammad (SAW) to Yatsrib," as evidenced by the calculation of the posttest results of the experimental class through the t-test, which meets the requirements, meaning there is an effect of Baamboozle media on the learning outcomes of SKI students.